(untitled) (Medico Legal Update, 2019)
Background/Objectives: The purpose of this study is to compare the stress response and the satisfaction of life to regular workers and non - regular workers. Method/Statistical Analysis: Data collection was conducted from July 1 to 31, 2017 for 600 workers of K company. Analysis was performed using the SPSS 23.0 version program and analyzed by ?2-test, t-test, ANCOVA and Pearson’s correlation coefficient. Findings: The results showed that the stress response was higher in the irregular workers than in the regular workers (f=11.09, ?=.001). In the stress response, the irregular workers showed higher somatic symptoms (f=6.18, ?=.013), depression (f=13.70, ?=.001) and anger (f=6.15, ?=.013) than the regular workers. Stress response and life satisfaction showed significant negative correlation (r= -. 387, ? <.001). Improvements/Applications: Workplaces need to pay attention not only to regular workers but also to the stress of non-regular workers, and to programs that improve their life satisfaction and alleviate stress reactions.